Penerapan Model DeLone dan McLean dalam Menilai Keberhasilan Sistem Informasi Manajemen di Sektor Publik - Rohim, Rika (Syntax Idea, 2025)
The implementation of management information systems (MIS) in the public sector plays an important role in improving the efficiency, transparency, and accountability of public services. To assess the success of MIS implementation, the DeLone and McLean model is used as an evaluation framework that includes six main dimensions: system quality, information quality, service quality, usage, user satisfaction, and net benefits. This study aims to analyze the extent to which these factors contribute to the success of MIS in the public sector. Using a quantitative approach, data were collected through a survey of government employees who use MIS in administrative and public service tasks. The results showed that system quality and information quality have a significant influence on user satisfaction, which ultimately increases the level of system usage. In addition, service quality is also an important factor in ensuring optimal technical support for users. Furthermore, the net benefits obtained from MIS, such as increased work efficiency, reduced administrative errors, and ease of data access, also strengthen the effectiveness of the system in supporting public sector performance. This study confirms that the implementation of the DeLone and McLean model can provide comprehensive insights in evaluating the success of MIS in the public sector. The recommendations provided include improving system quality through optimizing features and security, improving user service support, and regular training for employees to increase technology adoption. Thus, MIS can contribute more to the digital transformation of the public sector and improving the quality of service to the community.